An ex vivo Model of HIV-1 Infection in Human Lymphoid Tissue and Cervico-vaginal Tissue - Introini, Andrea (Bio Protoc, 2014)
Human tissue explants are a valuable tool to study the interactions between host and infectious agents. They reliably mimic many important aspects of tissue cytoarchitecture and functions and allow us the investigation of the mechanisms of microbial pathogenesis under controlled laboratory conditions. One of the advantages of this system is that, unlike isolated cells, infection of tissue blocks with HIV-1 does not require exogenous stimulation with mitogens or activating factors. Here we describe a protocol to infect with HIV-1 human lymphoid tissue from tonsils and cervico-vaginal tissue and maintain them in culture in a non-polarized setting. These ex vivo infected tissues can be used as fruitful models to study HIV-1 pathogenesis and HIV-1 vaginal transmission, respectively, as well as an efficient platform for testing anti-HIV therapeutic and preventative strategies.